SANGIRAN ANCIENT SITE AS A BATIK MOTIF IDEA AT “LIANASARI” CRAFTSMAN IN KLIWONAN VILLAGE, SRAGEN REGENCY - Syafi’, Muhammad; Gunadi (Eduarts: Jurnal Pendidikan Seni, 2025)
Sangiran Batik is a cultural heritage from ancestors originating from Sragen Regency, Central Java. The Sangiran Batik motif is inspired by various prehistoric discoveries at the ancient Sangiran site which has been recognized by UNESCO as a world cultural heritage. However, the general public's knowledge about Sangiran Batik is still minimal and not many craftsmen make it because the Sangiran Batik motif is classified as an old motif. However, there are also craftsmen who are aggressively developing batik motifs inspired by the Sangiran ancient site, namely the "Lianasari" Production House. This research aims to describe the development of batik at the "Lianasari" Production House and analyze the application of the Sangiran ancient site as a batik motif. The research method used is a qualitative descriptive research approach technique with data collection through observation, interviews, and documentation, as well as data analysis which includes data collection, data reduction, data presentation, drawing conclusions, and verification. The research results show that the development of batik at the "Lianasari" Production House reflects the cultural heritage of local craftsmen and the creativity of batik craftsmen in Kliwonan Village represents the rich history and natural surroundings. "Implementation of the Sangiran ancient site as a batik motif in the Production House" There are 4 Lianasari motifs, namely ancient ivory elephant motifs, ancient humans, ancient elephants and ancient tigers. Various innovations have been carried out in an effort to introduce Sangiran Batik to the wider community, such as marketing in various sectors and developing motifs into modern patterns.